PEMANFAATAN ENERGI PANAS BUMI UNTUK RANCANG BANGUN DAN PEMASYARAKATAN ALAT PENGERING HASIL PERTANIAN DAN PERKEBUNAN - Hendrasto, Fajar; Sumotarto, Untung; Meirawaty, Mira; Guntoro, Agus; Fakhmi, Nyco (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2025)
Indonesia has considerable potential for its 23.36 MW geothermal energy resource. The resource is utilized not only for indirect uses, such as electric power generation but also for direct uses, such as hot water pool purposes. Traditional drying, which relies on heat energy from the sun, can only be done during the day, and if it rains, drying is hampered. A continuous drying process can produce products with the water content that is not reduced efficiently. The use of geothermal energy can maintain the continuity of the drying process because the heat flow is stable and continuous compared to sunlight. An oven-shaped dryer by the FTKE Community Service Team (PkM) that uses the geothermal energy has been installed and introduced to the community in Ciparay Village, Pamijahan District, Bogor, Wes Java. This PkM Activity aims to provide examples and socialize geothermal energy-powered drying ovens for drying agricultural and plantation products. The method is to survey geothermal energy potential, conduct design work, and introduce a drying oven for agricultural products. This tool is hoped to help local communities dry agricultural and plantation products, such as tea leaves, grains, and various other agricultural and plantation products. With these result, it is hopes that this tool can be used by group of farmers and planters in other locations with geothermal energy resources. The PkM FTKE team has applied a similar drying tool in geothermal prospect areas in the Cisolok (Sukabumi), Batukuwung (Serang), and Ciseeng-Parung (Bogor).